The mediating influence of job satisfaction on the relationship between HR practices and cyberdeviance - Al-Shuaibi, Ahmad Sai’d Ibrahim; Subramaniam, Chandrakantan; Mohd Shamsudin, Faridahwati (International Journal of Global Business (IJGB), 2014)
Despite the many advantages and benefits the Internet offers to the workplace, it also allows people to misuse it while at work.Misusing the Internet during work hours for non-work related purposes is referred to as cyberdeviance.As our theoretical understanding of cyberdeviance is still limited, the purpose of this paper is to explore the role of HR practices in influencing cyberdeviance.It also seeks to examine whether job satisfaction mediates the link between HR practices and cyberdeviance.A survey of 273 administrative employees in four universities in Jordan, who were randomly selected using a cluster technique, was conducted.Frequencies, descriptive statistics, correlation, multiple regression, and hierarchical regression analyses were performed to analyze the data. Factor analyses revealed four dimensions of HR practices i.e. performance appraisal, compensation practice, career advancement, and employment security, while job satisfaction yielded two dimensions i.e. satisfaction with pay, and satisfaction with workload.Results showed that all four dimensions of HR practices were significantly able to explain 68.8% of the variance in cyberdeviance. Satisfaction with pay was found to partially mediate the link between performance appraisal and cyberdeviance.On the other hand, satisfaction with workload was a partial mediator between performance appraisal and cyberdeviance, and between career advancement and cyberdeviance. Recommendations for future research and practice, and limitations of the study are also highlighted.